Validação e adaptação transcultural do Perceived Efficacy and Goal Setting System PEGS para crianças brasileiras - Carina Iracema Bigonha Ruggio (2008)
There is today one strong trend for the enrollment of the occupational therapy in the client-centered practice. This model demands the instrumentations use that allows the participation of the child and the family in the definition of goals for the treatment. The literature has pointed evidences that the young child has ability to self-report and to determine goals to treatment. The interest to translate the Perceived Efficacy and Goal Setting System - PEGS is way there is not Brazilians instruments that allow the occupational therapist, who acts in the child development area, to insert in the context of client-centered practice.Objective: To verify if Brazilian children, of different ages, students from public and private school, understand the cards of the Perceived Efficacy and Goal Setting System PEGS, if they are able to indicate their abilities and if there might be any cultural bias. We also examined if the children maintained goal stability, the internal consistency of the scales and if there were significant differences between the childrens self-perception of ability and the perception of the caretakers and teachers. Methods: At the first moment, the PEGS questionnaires were translated and adapted considering semantic and cultural aspects. Eight children, ages six to nine years old, divided in two groups of 40 children from public schools as 40 from private ones, all from the metropolitan region of Belo Horizonte, as well and their parents and teacher responded to the translated PEGS questionnaires. The groups were paired by age, gender and type of school. Data analysis included calculation of the Cronbach to determine the internal consistency of the scales. As the Shapiro-Wilks test did not indicate the normality of the data set, the Friedmans test was used to test for significant differences between the childrens self-perception and the perception of the caretakers and teachers. The Mann-Whitney and Kruskal-Wallis tests were used to examine the relationship between the total percent scores and the childs age, gender and type of school. The Kappa coefficient was used to examine the agreement between children, caretakers and teacher on the scores of individual items of the PEGS. The goal stability was examined by counting the number of coincident goals over the two applications of the instrument. Multivariate CART analysis was used to describe the relationship between the variables (i.e., age, gender and school) on the determination of the childrens scores. Results: The children, caretakers and teachers did not have difficulties to understand the PEGS items. There were no significant difference between the childrens perception of efficacy and the perception of the caretakers and teachers, as well as no differences were found in the total percent scores as a result of age, gender and type of school influence. The Cronbachs coefficient indicated that the PEGS scales present good internal consistency. All children tested twice for the determination of goal stability chose at least one goal they had selected on the previous interview. Conclusion: The results suggest that Brazilian children are able not only to respond to the questionnaire, but they also can determine treatment goals. The instrument has potential for clinical use with Brazilian children, therefore the continuity of the validation process is recommended.